TOURISM SATELLITE ACCOUNT, A STATISTICAL TOOL TO ANALYSE TOURISM ROLES - Made Wiyasha, Ida Bagus (Pusat Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Nusa Dua Bali, 2004)
This article tries to explore Tourism Satellite Account (TSA) results in severalcountries. It is a statistical tool used to derive tourism multiplier in a countryseconomy. In preparing a TSA an input-output model is applied. Resultsshow differences in tourism roles in a countrvs economy due to the sizeand leakage in tourism